The feasibility and effectiveness of remote cognitive training on cognitive function and work performance in workers - Shibaoka, Michi; Masuda, Masashi; Iwasawa, Satoko; Ikezawa, Satoru; Eguchi, Hisashi; Nakagome, Kazuyuki (Frontiers in Psychology, 2024)
Objectives We aimed to determine whether remote cognitive training (CT) is feasible and has the potential to improve cognitive function and work performance in Japanese workers. Methods From June to September 2020, this intervention time series study enrolled workers aged 18–65 years from 10 companies located in a metropolitan area of Japan. Cognitive function tests and self-administered questionnaires were completed by the participants three times: at baseline, after 12 weeks of CT, and after a further 12 weeks following cessation. We measured work performance with the question: “How would you rate your performance (compared with your optimum performance) over the past 4 weeks?” Responses were made via a visual analog scale (0–100). Cognitive function was assessed using the THINC-integrated tool, which is a brief, objective computerized cognitive assessment battery. For our computerized remote CT intervention, BrainHQ was used on the basis of our scientific rationale and the empirical literature. We recommended three 20-min sessions of BrainHQ per week and sent participants three reminders. Results In total, 119 participants were recruited to this study. Only 22.7% of the subjects achieved the recommended training time of 720 min over 12 weeks. The median training time was used to divide participants into long and short- training groups. The long-training group showed a greater improvement in attention and executive function than the short-training group but there was no significant improvement in work performance after CT compared to baseline. Conclusion Our results suggest that although remote CT was not feasible enough, the effects on cognitive function can be expected by increasing training time and motivation.